Personal Time : Art of Estonia, Latvia and Lithuania 1945-1996. - Bernstein, Boris; Helme, Sirje; Komissarov, Eha; Liivrand, Harry; Luuk, Tamara; Saar, Johannes; Talvistu, Tiiu; Treier, Heie; Varblane, Reet (Warszawa : Galeria Zacheta, 1996)
Kits, Elmar ; Roode, Henn ; Sarapuu, Lembit ; Sooster, Ulo ; Meel, Raul ; Vint, Tonis ; Lapin, Leonhard ; Keskküla, Ando ; Okas, Jüri ; Runge, Sirje ; Rajangu, Raul ; Toomik, Jaan ; Laimre, Marko ; F.F.F.F.
biog. p. 74-81
Engels
Personal Time : Art of Estonia, Latvia and Lithuania 1945-1996, The Zacheta Gallery of Contemporary Art, Warszawa, 9 September - 13 October 1996 ; Centre for Contemporary Art Ujazdowski Castle, Warsaw
kunstcatalogus
Keywords: Estland